Odpowiedź :
POZIOM A
[tex]a)\\|AB|=\sqrt{(1-1)^2+(4-2)^2}=\sqrt{2^2}=\sqrt4=2\\|BC|=\sqrt{(-2-1)^2+(4-4)^2}=\sqrt{(-3)^2}=\sqrt9=3\\|CD|=\sqrt{(-2+2)^2+(0-4)^2}=\sqrt{(-4)^2}=\sqrt{16}=4[/tex]
[tex]b)\\|AB|=\sqrt{(3-1)^2+(5-5)^2}=\sqrt{2^2}=\sqrt4=2\\|BC|=\sqrt{(3-3)^2+(-2-5)^2}=\sqrt{(-7)^2}=\sqrt{49}=7\\|CD|=\sqrt{(2-3)^2+(-2+2)^2}=\sqrt{(-1)^2}=\sqrt1=1[/tex]
[tex]c)\\|AB|=\sqrt{(1-3)^2+(2-2)^2}=\sqrt{(-2)^2}=\sqrt4=2\\|BC|=\sqrt{(1-1)^2+(0-2)^2}=\sqrt{(-2)^2}=\sqrt4=2\\|CD|=\sqrt{(-7-1)^2+(0-0)^2}=\sqrt{(-8)^2}=\sqrt{64}=8\\[/tex]
[tex]d)\\|AB|=\sqrt{(4-1)^2+(6-6)^2}=\sqrt{3^2}=\sqrt9=3\\|BC|=\sqrt{(-2-4)^2+(6-6)^2}=\sqrt{(-6)^2}=\sqrt{36}=6\\|CD|=\sqrt{(-2+2)^2+(0-6)^2}=\sqrt{(-6)^2}=\sqrt{36}=6\\[/tex]
POZIOM B
[tex]a)\\|AB|=\sqrt{(2-1)^2+(5-3)^2}=\sqrt{1^2+2^2}=\sqrt{1+4}=\sqrt5\\|BC|=\sqrt{(5-2)^2+(1-5)^2}=\sqrt{3^2+(-4)^2}=\sqrt{9+16}=\sqrt{25}=5\\|CD|=\sqrt{(2-5)^2+(4-1)^2}=\sqrt{(-3)^2+3^2}=\sqrt{9+9}=\sqrt{18}=3\sqrt2[/tex]
[tex]b)\\|AB|=\sqrt{(-9-3)^2+(2+3)^2}=\sqrt{(-12)^2+5^2}=\sqrt{144+25}=\sqrt{169}=13\\|BC|=\sqrt{(-7+9)^2+(-2-2)^2}=\sqrt{2^2+(-4)^2}=\sqrt{4+16}=\sqrt{20}=2\sqrt5\\|CD|=\sqrt{(-3+7)^2+(-3+2)^2}=\sqrt{4^2+(-1)^2}=\sqrt{16+1}=\sqrt{17}[/tex]
[tex]c)\\|AB|=\sqrt{(-2+2)^2+(1+2)^2}=\sqrt{3^2}=\sqrt9=3\\|BC|=\sqrt{(4+2)^2+(-7-1)^2}=\sqrt{6^2+(-8)^2}=\sqrt{36+64}=\sqrt{100}=10\\|CD|=\sqrt{(-1-4)^2+(-19+7)^2}=\sqrt{(-5)^2+(-12)^2}=\sqrt{25+144}=\sqrt{169}=13[/tex]
[tex]d)\\|AB|=\sqrt{(2-3)^2+(-1+2)^2}=\sqrt{(-1)^2+1^2}=\sqrt{1+1}=\sqrt2\\|BC|=\sqrt{(1-2)^2+(9+1)^2}=\sqrt{(-1)^2+10^2}=\sqrt{1+100}=\sqrt{101}\\|CD|=\sqrt{(-1-1)^2+(4-9)^2}=\sqrt{(-2)^2+(-5)^2}=\sqrt{4+25}=\sqrt{29}[/tex]